The Atlantic Charter (Franklin and Eleanor Roosevelt Institute <Hyde Park, NY>: The Franklin and Eleanor Roosevelt Institute series on diplomatic and economic history, 1994)
In August 1941 Churchill and Roosevelt met in a secluded bay off the coast of Newfoundland. It was the first of their wartime meetings and in many respects the most significant. The document that was created at that meeting, the Atlantic Charter, proclaimed the two leaders' vision of a new world order, a set of principles that would govern international relations with the coming of peace. This remarkable collection of essays is the result of an international conference of American, British, and Canadian scholars held at Memorial University of Newfoundland that marked the fiftieth anniversary of the historic meeting. The essays discuss both the Charter's formulation and its long-term significance and provide fascinating perspectives on the Second World War and its aftermath.